Analisis Komparasi Terhadap Efektivitas Penyelenggaraan Pemilihan Umum Serentak Antara Indonesia Dan Brazil - Puji Purnama Sari; Pradana, Syafa'at Anugrah; Abdul Hafid (Program Studi Hukum Tata Negara, Institut Agama Islam Negeri Parepare, 2024)
This research discusses the effectiveness of simultaneous elections in Indonesia and Brazil. The objectives of this study are to describe the effectiveness of simultaneous elections in Indonesia and Brazil and to outline an ideal model of simultaneous elections for Indonesia. The results of this study indicate that: 1) Regarding the effectiveness of simultaneous elections, Brazil's system proves to be more effective than Indonesia's. In Indonesia, the voting and vote-counting processes still use a direct method with paper ballots, and dispute resolution follows a tiered complaint system. In contrast, Brazil employs electronic voting machines for both voting and vote counting, while also implementing a tiered system for election dispute resolution. The effectiveness of simultaneous elections in Indonesia could be improved by adopting processes similar to those used in Brazil's simultaneous election system. 2)The ideal model of simultaneous elections for Indonesia would involve holding elections once every five years, encompassing national elections for members of the House of Representatives (DPR), Regional Representative Council (DPD), and President/Vice President concurrently. This would be followed by local/regional elections held sometime later for members of Provincial and Regency/City Regional People's Representative Councils (DPRD), as well as for Governors and Regents/Mayors. This model aims to strengthen the presidential system, provide election organizers with more focused preparation and management time, reduce complex logistical and administrative burdens, and enhance transparency and voter participation.